Influence of Opening Up Daycare and Day Camps on Resurgence Potential of COVID-19 Pandemic: Assessing Infectivity Potential From Youth in Ontario, Canada - Snider B; Phillips P; McBean EA; Gadsden SA; Yawney J (Institute of Electrical and Electronics Engineers (IEEE), 2021)
Concerns regarding the impact of opening daycares and day camps are examined to explore the sensitivity on outbreaks of COVID-19. Overall, while controlling the spread of COVID-19 must be a major concern for all people, society needs to consider various options, including those of alternative reopening strategies to reflect both the impact on children when reopening of daycares/day camps but also the potential impact on viral growth transmittance. Infectivity modeling scenarios are described for the province of Ontario, indicating how the caseloads may reverberate through the population in response to the opening of daycare and summer day camps. An SEIR model, stratified by age, is used to model the primary compartments of the virus. The results show that the spread of COVID-19 reached a peak in April 2020 and steadily declined for Toronto and Peel Public Health Units (PHUs). Furthermore, the model indicates that reducing daycare and day camp capacities by 50% results in more than a 75% reduction in impacts on caseload and deaths, relative to not undertaking due care and diligence to control the virus growth. The findings indicate that combining reduced capacity with effective social distancing parameters is expected to be the most effective in reducing additional caseloads associated with reopening daycare and day camps within Ontario. By reducing capacity and contact rates by 50% through social distancing protocols, additional cases are expected to reduce by 88% for Toronto and 91% for Peel PHUs. These results highlight the importance of both reducing daycare/day camp capacity and managing social distancing protocols that are effective measures to help control the spread of COVID-19 within Ontario.
Keywords: 37 Earth Sciences; 4203 Health Services and Systems; 42 Health Sciences; Emerging Infectious Diseases; Coronaviruses; Infectious Diseases; 3 Good Health and Well Being